The resocialization of the recidivist in the foundations of the criminal sentence. Tacna criminal courts case. 2013-2014 period - Aguilar Coronel, Jose Sergio (2020)
The problem arises when it comes to condemn a recidivist of the crime, the grounds of the sentence - with respect to the justification and quality of the recidivist agent -, are scarce. The end of the sentence of the sentenced recidivist is not justified, bearing in mind that modern criminal law establishes that the purpose of punishment is the re-socialization of the individual. The investigation was carried out in accordance with 20 criminal judgments of the Judiciary of Tacna, which allowed to fully know the reality of the pronouncements and grounds of the criminal judges of this jurisdiction. When the objectives are achieved, this research acquires importance and legal relevance because it increases the knowledge of science in legal matters with scientifically proven empirical contributions on the basis of re-socialization as the end of the penalty for repeat offenders. Methodologically, the research is quantitative and qualitative. Likewise, the present investigation will be purely documentary (condemnatory sentences). The measurement instrument is represented by the statement information card. It is concluded that the foundation of criminal sentences regarding resocialization as the end of the sentence for the recidivists, in the Criminal Courts of Tacna, contain an insufficient motivation. The suggestions are aimed at improving the grounds of the judgments and on the application of penalties. to the recidivists the Congress of the Republic should take actions to modify on recidivism